2020
DOI: 10.1177/0825859720951661
|View full text |Cite
|
Sign up to set email alerts
|

Care Considerations in a Patient- and Family-Centered Medical Assistance in Dying Program

Abstract: Background: Medical Assistance in Dying (MAID) became legal in Canada in June 2016. As part of a project designed to improve end-of-life care for those requesting MAID, qualitative data from patients, families, and providers were used to assess opportunities to enhance patient-and family-centered care (PFCC) in this program. Methods: Thirty interviews were conducted with patients, families, and healthcare providers. Five patients who requested an assessment for MAID, 11 family members, and 14 healthcare provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…The findings from this study also point to the potential for vulnerabilities family members may experience. Providing MAiD to patients with capacity loss may further complicate the grief they experience [ 8 , 40 , 41 ]. Early, transparent communication with family members about patients’ wishes and follow-up visits with patients and their families can help minimize family members’ risk for complicated grief [ 8 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from this study also point to the potential for vulnerabilities family members may experience. Providing MAiD to patients with capacity loss may further complicate the grief they experience [ 8 , 40 , 41 ]. Early, transparent communication with family members about patients’ wishes and follow-up visits with patients and their families can help minimize family members’ risk for complicated grief [ 8 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Providing MAiD to patients with capacity loss may further complicate the grief they experience [ 8 , 40 , 41 ]. Early, transparent communication with family members about patients’ wishes and follow-up visits with patients and their families can help minimize family members’ risk for complicated grief [ 8 , 40 ]. However, such measures require time and resources that many lack [ 32 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was also a need to manage the relational challenges that arose between those who saw MAID as an acceptable moral option and those who did not [19-21, 25, 26]. Caring for families throughout the process and into bereavement has consistently been one of the most challenging aspects of MAID [20,28,29]. Given the potential impact of these factors on the quality of care provided through MAID, and on the ongoing debate about the relationship between MAID and palliative care, it is important to understand how MAID is evolving over time within a larger systems perspective.…”
Section: Request Signed By One Independent Witnessmentioning
confidence: 99%
“…29 Therefore, many studies suggested that additional roles and responsibilities can be addressed by an interdisciplinary care team, which includes social workers, spiritual care providers, specialised nurses or even 'death doulas'. 23 24 36 Ultimately, when considering how HCPs can 'support the circle of support,' 24 greater structure, funding and resources are needed. Currently, the full obligation and duration of the relationship between HCPs and family/friends is ambiguous and variable.…”
Section: With Healthcare Providersmentioning
confidence: 99%